The ECM path of senescence in aging: components and modifiers. (20th March 2020) - Levi, Naama; Papismadov, Nurit; Solomonov, Inna; Sagi, Irit; Krizhanovsky, Valery
Abstract : The extracellular matrix (ECM) is a key noncellular component in all organs and tissues. It is composed of a large number of proteins including collagens, glycoproteins (GP), and ECM‐associated proteins, which show diversity of biochemical and biophysical functions. The ECM is dynamic both in normal physiology of tissues and under pathological conditions. One cellular phenomenon associated with changes in both ECM components expression and in ECM remodeling enzymes secretion is cellular senescence. It represents a stable state form of cell cycle arrest induced in proliferating cells by various forms of stress. Short‐term induction of senescence is essential for tumor suppression and tissue repair. However, long‐term presence of senescent cells in tissues may have a detrimental role in promoting tissue damage and aging. Up to date, there is insufficient knowledge about the interplay between the ECM and senescence cells. Since changes in the ECM occur in many physiological and pathological conditions in which senescent cells are present, a better understanding of ECM‐senescence interactions is necessary. Here, we will review the functions of the different ECM components and will discuss the current knowledge about their regulation in senescent cells and their influence on the senescence state. Abstract : One cellular phenomena associated with changes in the extracellular matrix (ECM) is cellular senescence. The interplay between the ECM and senescent cells is complex and requires further investigation. Changes in the ECM occur in many physiological and pathological conditions in which senescent cells are present and secrete components of senescence associated secretory phenotype that interact with ECM. Here, we review current knowledge about the different ECM components and their regulation in senescence state.